Association of different intensities of physical activity in children with parental support - Wang, Siyan; Zhou, Xiuxiu; Li, Kai (Frontiers in Psychology, 2025)
ObjectiveTo investigate the status of physical activity and parental support of children aged 6–10 years in Macau and to explore the relationship between them.MethodsThe International Physical Activity Questionnaire-Short form (IPAQ-S) and Activity Support Scale for Multiple Groups (ACTS-MG) were used to investigate children’s physical activity time, parental support level, and general demographic information. The height and weight of the children are measured by a portable instrument.ResultsThe physical activity of children in Macau is insufficient, does not meet the guidelines of the World Health Organization (WHO). Regarding parents’ support, the average score of physical activity models and community resource utilization is relatively low. Linear regression results showed that the relationship between low physical activity (LPA) and parental support was not statistically significant, and that children with moderate physical activity (MPA) (over all β = 0.256, boys β = 0.245, girls β = 0.279), moderate-to-vigorous physical activity (MVPA) (over all β = 0.291, boys β = 0.279, girls β = 0.312) were significantly positively correlated with logistical support. Boys’ vigorous physical activity (VPA) (β = 0.335) was significantly positively correlated with community resource utilization, and girls’ vigorous physical activity (VPA) (β = 0.268) was significantly positively correlated with physical activity models.ConclusionMacau parents generally pay attention to children’s physical activity endeavors, but the level of children’s physical activity is relatively low. There are certain differences in the relationship between the types of parental support and the physical activity of children of different genders, and the relationship between parental logistical support and children’s physical activities is closer. In future studies, investigators could look at various family interventions and make more targeted plans based on gender and activity intensity.